Personalized Cancer Medicine: Are We There Yet?. (19th May 2013) - Lawler, Mark; Selby, Peter
Abstract : Personalized cancer medicine is at a crucial phase of development. This month's edition focuses on how innovation and the development of personalized medicine can positively influence disease outcomes–but at what price?